A valorização e a precarização do trabalho docente: um estudo de políticas públicas a partir de 1990 - Wonsik, Ester Cristiane (2013)
This dissertation investigates policies for teaching work in Brazil. The object of study refers to the conditions of teaching deriving from policies developed since 1990. It originates from the observation that, on one side, based on the legal requirements, there is a speech of teacher valorization, on the other hand, guiding to an increasing recariousness of the work. As a general objective, We analyze the changes in the conditions of teaching and the consequences for the practice of educational activities, resulting from neoliberal alignment policies, established in educational reforms undertaken in international and national levels. It is adopted the method and the analytical categories of historical and dialectical materialism, by allowing understand tensions, the intentions, processes and most general elements in its relationship with the teaching work. We seek to understand if the precariousness and the valorization present in the policies are contradictory or combined aspects. For mediation of bibliographical and documentary analysis, we explain the references supposedly reporting to teachers valorization in the first section. The second section analyzes the implications of the policy of valorization brought to the working conditions of teachers. It is observed that in the conduction of international and Brazilian educational policy, the supposed value of teaching was accompanied by the construction of a new profile of this professional, appropriate to the new forms of precarious work conditions, manifested by flexibility, by dismantling rights, the weakening of representations, among others. It is also learned the speech of valorization as a means of ensuring consensus, acceptance or conformity of these professionals regarding the changes experienced in their working conditions. The third section analyzes the new forms of precarious work of teaching category as a condition intrinsically linked to changes in the world of labor in general. The capitalist economic crisis from the late 1970s decade is investigated, the strategies designed to overcome them and the consequences for the world of labor since then. It is verified that political and economic interdependence between nations has generated and disseminated structural reforms that, by introducing new forms of regulation and State action, produced changes both relating to the rights and working conditions in general and relating to teachers in particular. In the case of the conditions of teachers' work, the precariousness criteria were underlying the speech of valorization on the conduction of educational policies. It is concluded there is an inseparability between valorization and precariousness politics of teaching routed in the 1990s, which shows that the contradictory nature of these policies was only apparent and, in essence, valorization and precariousness, expressing capitalist relations, are not in opposition, but are linked, in that sense, it is said they are different expressions of the same policy. It is noteworthy that, in the course of history, laws and conditions placed on teachers-workers are not natural nor eternal, but are produced by the contradictory movement of society, and depend on both the historical conditions that produced them as those to be forged from multiple competing projects in the social totality.